Passenger’s Satisfaction with their Travel- Comparison of Haryana Roadways Transport Corporation and Private Buses - *, Smriti; Boora, Dr A S (IJRDO - Journal of Social Science and Humanities Research, 2018)
The public bus transport is much more needed in metropolitan cities and it also connects different categories of people from different places. So it is very important for any city to have an effective public transportation system and the same has to be managed to face upcoming, future challenges and to ensure effectiveness in their operations, service quality to satisfy the unpredictable expectations of the passengers from different segments. Now, the major city like Gurgaon is heavily stressed to keep pace with the demand for Bus Transportation system to go with economic growth and infrastructural development. With a rise in demand for adequate public bus transportation system and increase in population size, it may create and insist on the transport sectors to have higher and good quality of transport service. But it also creates overcrowding at the bus terminus and it will be the main cause of many service-related problems.